Controlled-release fertilizers with an ultralow coating content. Issue 9 (6th February 2023) - Liang, Dunsheng; Shi, Hebo; Lu, Qiming; Quirino, Rafael L.; Zhang, Chaoqun
Abstract : The controlled-release fertilizers with superior controlled-release performance and an extremely low coating content were fabricated using castor oil-based polyurethane coatings, followed by dual superhydrophobic modification. Abstract : Although bio-based polymers have been found to be promising coating candidates for controlled-release fertilizers (CRFs), high coating contents are always required to form an efficient physical barrier for achieving desirable release control. Here, a novel polymer nano-coating was prepared for controlled-release fertilizers from plant oil-based polyurethanes, followed by dual superhydrophobic modification with nano-stearic acid-Mg(OH)2 and paraffin wax. The coatings demonstrated superhydrophobicity in the beginning of the release process and maintained "dynamic superhydrophobicity" even after the expansion of polymer coated fertilizers during the fertilizer release process. The CRFs coated with only 1.5 wt% superhydrophobic coating achieved a N release longevity of 33 days, constituting the lowest coating content reported to date. The dual modification technique for dynamic superhydrophobic coating is a novel and effective strategy for large-scale production of bio-based CRFs with an ultralow coating content that can effectively decrease their cost and facilitate further application.